Generation mechanism of linear and angular ball velocity in baseball pitching - Koike, S.; Uzawa, H.; Hirayama, D. (Proceedings, 2018)
The purpose of this study was to quantify the functional roles of the whole-body`s joint torques including fingers` joints in the generation of ball speed and spin during baseball fast-ball pitching motion. The dynamic contributions of joint torque term, gravitational term, and motion-dependent term (MDT) consisting of centrifugal force and Coriolis force, to the generation of the ball variables were calculated using two types of models. Motion and ground reaction forces of a baseball pitcher, who was instructed to throw a fastball into the target, were measured with a motion capture system with two force platforms. The results showed (1) the MDT is the largest contributor to ball speed (e.g., about 31 m/s prior to ball release) when using 16-segment model, and (2) the horizontal adduction torque of pitching-side shoulder joint plays a crucial role in generating ball speed with conversion of the MDT into other terms using a recurrence formula.